Bosnian Identity – Myth And/Or Reality - Zekić, Marinko (Slavica Lodziensia, 2017)
The rich socio-cultural history of Bosnia and Herzegovina as a single territorial, political, state and legal and administrative rounded whole, can be seen in several separated simultaneous fl ows arising as a result of the deep-rooted ethno-confessional division of this area, where religion, as the dominant integrating cultural factor, also represented the main distinctive element of the national identity of the three Bosnian constituent peoples, which the unaltered state agrees with to this day. As a unique area with religions at the border, and denominational boundaries at the edges of Catholicism and Orthodoxy among which Islam is wedged between, Bosnia and Herzegovina represents a unique civilizational bridge between East and West, where the followers of these religions see as their guardians, highlighting specifi c religious, cultural and national characteristics which establishes the opposition to the “other” and “diff erent” with which for centuries has coexisted. The most prominent features of identity and otherness which exist in symbiosis are articulated precisely on the borders as places of their meetings, which in turn have never been so impervious to keep the integration of diff erent ethnic and religious traditions followers, leading to ghettoisation and creating worlds closed for themselves, and long-term coexistence of diff erent and often confl icting civilizational-religious system characterized by a certain closeness of high culture of individual entities and openness, and mutual intertwining of which was out of the realm of popular culture.